Inflammatory Mediators Drive Adverse Right Ventricular Remodeling and Dysfunction and Serve as Potential Biomarkers - Sydykov, Akylbek; Mamazhakypov, Argen; Petrovic, Aleksandar; Kosanovic, Djuro; Sarybaev, Akpay S.; Weissmann, Norbert; Ghofrani, Hossein A.; Schermuly, Ralph T. (Frontiers in Physiology, 2018)
Adverse right ventricular (RV) remodeling leads to ventricular dysfunction and failure that represents an important determinant of outcome in patients with pulmonary hypertension. Recent evidence indicates that inflammatory activation contributes to the pathogenesis of adverse RV remodeling and dysfunction. It has been shown that accumulation of inflammatory cells such as macrophages and mast cells in the right ventricle is associated with maladaptive RV remodeling. In addition, inhibition of inflammation in animal models of RV failure ameliorated RV structural and functional impairment. Furthermore, a number of circulating inflammatory mediators have been demonstrated to be associated with RV performance. This manuscript reviews the role of inflammation in RV remodeling and dysfunction and discusses anti-inflammatory strategies that may attenuate adverse structural alterations while promoting improvement of RV function.